PERAN BEA DAN CUKAI DALAM PENGAWASAN JASA TITIP ONLINE MELALUI BARANG BAWAAN PENUMPANG DI BANDARA INTERNASIONAL JUANDA - Ramadhan, Gilang; Astutik, Sri; Handayati, Nur (Jurnal Ilmiah Wahana Pendidikan, 2024)
Online personal shopper businesses that are increasingly in demand by Indonesian consumers must be accompanied by optimal monitoring from the relevant agencies, namely the Directorate General of Customs and Excise, to minimize online personal shoppers who use import duty exemption facilities. This study aims to determine the role of Customs and Excise in monitoring passenger luggage at Juanda International Airport, what violations are committed by online entrepreneurs, and how the perspective is in criminal law. Empirical research type with socio legal approach and qualitative descriptive research method. The results of this study are Customs and Excise conduct monitoring by analyzing x-ray and passenger profiles. The method of violation is splitting and deliberately not declaring the quantity and types of the items correctly. Online personal shopper who avoid paying import duties and do not fill out customs declarations correctly may be subject to criminal sanctions in accordance with the applicable regulations.